Vasoactive Intestinal Peptide Knockout (VIP KO) mouse model of sulfite-sensitive asthma: up-regulation of novel lung carbonyl reductase - Szema, Anthony M (BioMed Central, 2011)
BACKGROUND: We earlier reported spontaneous features of asthma in Vasoactive Intestinal Peptide knockout mice (VIP KO): 1) peribronchiolar airway inflammation, with accumulation of lymphocytes and eosinophils, 2) pro-inflammatory cytokine production of IL-5, IL-6, with IFN-γ, and 3) airway hyper-responsiveness to inhaled methacholine. In human asthma, a phenotype with sulfite sensitivity leads to airway inflammation and hyper-responsiveness to inhaled sulfites, and is associated with upregulation of anti-oxidant protein lung carbonyl reductase. For the present experiments, we examined the role of VIP in modulating anti-oxidant genes and their proteins, including lung carbonyl reductase. RESULTS: Four male VIP KO mice and four wild-type age- and gender matched mice had lungs examined for whole genome microarray and a proteomics approach using mass spectrometry. The proteomics analysis revealed that a novel variant of anti-oxidant protein lung carbonyl reductase (car3) was uniquely and markedly elevated in the VIP KO mice. RT-PCR indicated that carbonic anhydrase 3, which is an anti-oxidant protein, was elevated in the VIP KO mice. CONCLUSIONS: These data support the concept that VIP influences the endogenous oxidant/antioxidant balance. One potential implication is that VIP and its analogues may be used to treat inflammatory diseases, including asthma.